Pengaruh Fipronil Terhadap Kelimpahan Populasi dan Tingkat Parasitisasi Parasitoid Telur Penggerek Batang Padi Kuning di Kabupaten Tabanan - PUTRA, I GEDE FEBRIANTO MAHA; SUPARTHA, I WAYAN; WIDANINGSIH, DWI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
The Influence of Fipronil 50 g/l Against Population Abundance and Parasitization Level of Egg Parasitoid of Yellow Rice Stem Borer in Tabanan District Yellow rice stem borer, Scirpophaga incertulas Walker (Lepidoptera: Pyralidae), is one of the important pests of rice plants in Indonesia. Efforts to control those pests are using a lot of synthetic insecticide in the field, meanwhile egg parasitoid is considered to have an important role in the control those pests in nature. The aim of this research is to know the influence of insecticide with active ingredient Fipronil 50 g/l to population abundance and parasitization level of egg parasitoid of yellow rice stem borer. The research was arranged by using randomized block desing with six treatments and four replicates. The results showed that T. Schoenobii parasitoid is the most dominant parasitoid among other types of parasitoids and its diversity is low that is <1,5. Pesticide with active ingredient Fipronil 50 g/l has significant effect on population abundance and parasitization level egg parasitoid of yellow rice stem borer. The highest population abundance was on control and lowest in treatment dose 1.50 cc/l. The highest parasitoid parasitization rate in Tabanan is (19.70%). The parasitization rate was decrease with the increase of tested insecticide dose, so the lowest number was at 1.50 cc/l treatment with percentage (8.62%).